Angústia e Recompensa: narrativa crítico reflexiva sobre o meu desenvolvimento no curso de medicina - Montever, Daniel Cunha (Universidade Federal de São Carlos, 2024)
The final paper presents a critical-reflective narrative of the author about the medicine course at the Federal University of São Carlos and his impressions, experiences and feelings during the process. In its development, the work presents a narrative that exposes the course format, the author's experience in the course and the author's reflections on each aspect of the course. The development begins with the author's entry into the university, exposing his life at that moment and the feelings that surrounded and guided him in choosing the institution. The text moves on to address the first cycle, from enrollment in the course and the discovery of its different methodology, progressing to an explanation of its functioning, divided into three major areas of activities: Problem-Situation, Simulation Station, Professional Practice and Practice Reflection. The reflection that permeates the first cycle involves feelings of anguish, concern, and incapacity. Moving on to the second cycle, there are changes in the pattern of activities, both in content and in the ramification of the basic structures of the curricular grid compared to the first cycle. With a clearer gain in knowledge, the reflection presents the counterpoint of previous anxieties with the recognition in the knowledge construction advance and introduces new anxieties about the continuity of the process, although already accompanied by expectations that involve the student's development and evolution. When addressing the final cycle, the internship, the text diversifies due to the intensity that the period presents. Reflections and feelings also diversify and correspond to each stage present in the internship, which are: Medical Clinic, Pediatrics, Specialized Medical Outpatient Clinics, Gynecology and Obstetrics, General Surgery and Family and Community Health. The conclusion of the work presents a reflective synthesis where the author exposes his impressions of the entire experiential process and concludes with his personal opinions about his personal development and the influence of the course on his personal and professional formation.
Anguish and Reward: reflective critical narrative about my development in the medicine course
Keywords: Medicina; Reflexão; Narrativa; Formação; Desenvolvimento profissional; Metodologia; Internato; Medicine; Reflection; Narrative; Professional development; Methodology; Internship; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM